East meets West : human rights and democracy in East Asia - Bell, Daniel (Daniel A.) (Princeton, N.J. : Princeton University Press, 2000)
Is liberal democracy a universal ideal? Proponents of "Asian values" argue that it is a distinctive product of the Western experience and that Western powers shouldn't try to push human rights and democracy onto Asian states. Liberal democrats in the West typically counter by questioning the motives of Asian critics, arguing that Asian leaders are merely trying to rationalize human-rights violations and authoritarian rule. In this book--written as a dialogue between an American democrat named Demo and three East Asian critics--Daniel A. Bell attempts to chart a middle ground between the extremes of the international debate on human rights and democracy. Bell criticizes the use of "Asian values" to justify oppression, but also draws on East Asian cultural traditions and contributions by contemporary intellectuals in East Asia to identify some powerful challenges to Western-style liberal democracy. In the first part of the book, Bell makes use of colorful stories and examples to show that there is a need to take into account East Asian perspectives on human rights and democracy. The second part--a fictitious dialogue between Demo and Asian senior statesman Lee Kuan Yew--examines the pros and cons of implementing Western-style democracy in Singapore. The third part of the book is an argument for an as-yet-unrealized Confucian political institution that justifiably differs from Western-style liberal democracy. This is a thought-provoking defense of distinctively East Asian challenges to Western-style liberal democracy that will stimulate interest and debate among students of political theory, Asian studies, and international human rights
Cover13; -- Contents13; -- Acknowledgments -- INTRODUCTION -- PART I THE EAST ASIAN CHALLENGE TO HUMAN RIGHTS AND DEMOCRACY: REFLECTIONS ON EAST-WEST DIALOGUES -- TOWARD A TRULY INTERNATIONAL HUMAN RIGHTS REGIME -- 1. Trade-offs -- 1.1. Rights vs. Development: A Zero-Sum Game? -- 1.2. The Need for Specificity -- 2. An Asian Voice on Human Rights? -- 2.1. Human Rights: A Western Invention? -- 2.2. Increasing Commitment to Human Rights in East Asia: Strategic Considerations -- 2.2.1. On the Prospects of Exporting American Ideals to East Asia -- 2.2.2. Appealing to the Universal Declaration of Human Rights in Asia -- 2.2.3. Local Justifications for Human Rights -- 3. A Different Moral Standpoint? -- 3.1. Cultural Respect vs. Liberal Neutrality -- 3.2. Justifiable Constraints on Western-Style Rights -- 3.3. New 8220;Asian8221; Rights: Expanding the Set of Internationally Recognized Rights -- Summary -- DEMOCRATIC RIGHTS: ON THE IMPORTANCE OF LOCAL KNOWLEDGE -- 1. Trade-off Issues -- 1.1. On the Possibility of Decent Nondemocratic Regimes -- 1.2. The Costs of Democratization -- 2. Democratic Rights: Different Justifications -- 2.1. Limiting the Power of the State -- 2.2. Democracy as a Means for Nation-Building -- 2.3. Identifying the Agents of Democratization -- 2.4. Nation-Building and Social Consensus in Confucian Democracies -- 3. Democratic Rights: Different Constraints -- 3.1 Democracy vs. Civil Rights -- 3.2 Democracy vs. Social and Economic Rights -- 3.3 Democracy vs. Future Generations -- Summary -- PART II THE PROS AND CONS OF DEMOCRACY IN SINGAPORE: A FICTITIOUS DIALOGUE WITH LEE KUAN YEW -- IS LIBERAL DEMOCRACY SUITABLE FOR SINGAPORE? -- 1. Democracy Defined as Free and Fair Competitive Elections -- 2. Democracy Justified (Only) by Its Consequences -- 3. Democracy and Security -- 4. Democracy and Civil Liberties -- 5. Democracy and Prosperity -- Summary -- A COMMUNITARIAN CRITIQUE OF AUTHORITARIANISM: THE CASE OF SINGAPORE -- 1. Community and Democracy -- 2. Democracy and the Family -- 3. Democracy and the Nation -- 3.1. Singapore: A Patriotic Nation? -- 3.2. How Authoritarianism Undermines Patriotism -- 3.3. On the Need for Patriotism in Singapore -- Summary -- PART III DEMOCRACY WITH CHINESE CHARACTERISTICS -- A POLITICAL PROPOSAL FOR THE POST-COMMUNIST ERA -- 1. Constraining Democratic Populism -- 1.1. On the Need for Capable and Far-Sighted Rulers in Modern Societies -- 1.2. A Confucian Tradition of Respect for a Ruling Intellectual Elite -- 2. Alternative Proposals -- 2.1. Plural Voting Schemes -- 2.2. A Corporatist Assembly -- 2.3. A Parliament of Scholar-Officials -- 3. The Proposal -- 3.1. Selection Procedures -- 3.2. The Problem of Corruption -- 3.3. The Question of Universalizability -- 3.4. The Problem of Gridlock -- 3.5. Implementation of the Proposal -- Closing Scene -- Select Bibliography -- Index.
Includes bibliographical references (pages 337-352) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Human rights -- East Asia; Democracy -- East Asia; Droits de l'homme (Droit international) -- Extrême-Orient.; Démocratie -- Extrême-Orient.; POLITICAL SCIENCE -- Political Process -- General; Democracy; Human rights; East Asia; Samfundsvidenskab -- Politologi; History -- Methodology